Traumatic brain injury: rehabilitation - Almeida, Tatiane Lopes Teixeira; Falkenburg, Lilian; Nascimento, Roberta Zanardi Ruiz; Reis, Cristina Arruda; Sales, Viviane Carolina; Pedroso, Tatiana Domingues; Ceccato, Rebeca Boltes; Imamura, Marta; Battistella, Linamara Rizzo (Acta Fisiátrica, 2012)
This study revised articles from the MEDLINE (PubMed) databases and other research sources, with no time limit. To do so, the search strategy adopted was based on (P.I.C.O.) structured questions (from the initials "Patient"; "Intervention"; "Control" and "Outcome". With the above keywords crossings were performed according to the proposed theme in each topic of the (P.I.C.O.) questions. After analyzing this material, articles regarding the questions were selected and, by studying those, the evidences that fundamented the directives of this document were established.